Pelisanan Al-Qur’an: Tinjauan Estetika Kenikmatan Tekstual - Okta Firmansyah; Indira Kartini (Universitas Darussalam Gontor, 2023)
Similar to the language of the Qur'an, the terminology will imply pleasure before ideological submission. This study explores several hypotheses regarding the pleasure-related aspects of the Qur'anic text, particularly in the context of the oral Qur'an. It is because achieving an aesthetic experience through the mouth is one way. Some of these issues have been addressed by the concepts of work and text (teks), as well as Roland Barthes' aesthetics of textual pleasure (The Pleasure of the Text). The use of Barthes concepts is made to carry on semiotics' work in the study of how to read the Qur'an and incorporate the Barthesian text theory into the same study. In comparison to the findings of this qualitative research, the Qur'an as an authoritative holy book is a work that has absolute and complete truth and completeness, which does not allow any textual changes. Muslims who reject this idea are also rejecting their faith in Almighty Allah. Since the Qur'an is so full of meaning, which is limitless and can never be fully understood, it is also a text. In light of this, the Qur'an will give its readers ample room to create new texts (read: tafsir). This is consistent with the principle, ah likulli zaman wa makn, that the Qur'an will always be relevant to the world and its events. The Qur'an, which is mostly read by Muslims, will also make its readers happy at the same time.